Hubungan Pengetahuan dan Sikap Ibu Hamil dengan Frekuensi Kunjungan Antenatal Care di BPM Syukhriah Kota Langsa Provinsi Aceh Tahun 2024 - Wilzanur Eka Putri; Friza Novita Sari Situmorang; Ingka Kristina Pangaribuan; Parningotan Simanjuntak; Rismalia Tarigan (Quantum Wellness : Jurnal Ilmu Kesehatan, 2025)
Antenatal Care (ANC) examination is a series of activities carried out from conception until before the labor process begins, which is aimed at all pregnant women. Coverage of antenatal care visits is still low, which can increase maternal and neonatal complications as well as maternal and child deaths caused by high-risk pregnancies that are not immediately treated. In 2023, the highest birth assistance process by traditional midwives was in Gayo Lues Regency at 4.42 percent and Southeast Aceh Regency at 4.32 percent. This study aims to determine the relationship between the level of knowledge and attitudes of pregnant women and the frequency of antenatal care visits at BPM Syukriah, Langsa City, Aceh Province in 2024. This study used a Cross Sectional design, the research time was May-June 2024, with a population and sample of 34 people. The sampling technique used total sampling, the analysis test used the Chi Square Test. The majority of respondents who had poor knowledge and had an incomplete history of antenatal care visits were 16 people (47.1%), while the majority of respondents who had good knowledge and had a complete history of antenatal care visits were 9 people (26.5%). There is a significant relationship between the knowledge and attitudes of pregnant women with antenatal care visits at BPM Syukhriah, Langsa City, Aceh Province with a p value <0.05 (0.001).